Stakeholder perspectives on current determinants of ultrasound-guided thoracentesis in resource limited settings: a qualitative study - Jennifer Doran; Reem Hanna; Tatenda Nyagura-Mangori; Narayan Mahotra; Santa Kumar Das; Magaret Borok; Ali Musani; Anna M Maw (BMJ Open)
Objective Preprocedure pleural fluid localization using bedside ultrasound has been shown to reduce complications related to thoracentesis and is now considered the standard of care. However, ultrasound-guided thoracentesis (USGT) has not been broadly adopted in many low-resource settings. With increasing affordability and portability of ultrasound equipment, barriers to USGT are changing. The aim of this multisite qualitative study is to understand the current barriers to USGT in two resource-limited settings.Setting We studied two geographically diverse settings, Harare, Zimbabwe, and Kathmandu, Nepal.Participants 19 multilevel stakeholders including clinical trainees, attendings, clinical educators and hospital administrators were interviewed. There were no exclusion criteria.Primary outcome To understand the current determinants of USGT adoption in these settings.Results Three main themes emerged from these interviews: (1) stakeholders perceived multiple advantages of USGT, (2) access to equipment and training were perceived as limited and (3) while an online training approach is feasible, stakeholders expressed scepticism that this was an appropriate modality for procedural training.Conclusion Our data suggests that USGT implementation is desired by local stakeholders and that the development of an educational intervention, cocreated with local stakeholders, should be explored to ensure optimal contextual fit.